(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
DNA’s helix-coil transition with ethidium bromide (EtBr) has been investigated within the limits of ionic strength 2.2 ·10-3 M ≤ μNa+ ≤ 2.2·10-2 M. It was revealed that at some DNA-ligand ratios the transition width of complexes ΔT becomes equal to the width of “free” DNA Δ0T. It was shown that equalization takes place depending on the ionic strength of solution.